Development of fragility curves for confined masonry buildings in Lima, Peru - Lovon, Holger (2018)
This paper aims at investigating the seismic fragility of confined masonry (CM) structures in Lima, Peru, which can be used to perform earthquake scenarios at urban scale. A database describing the geometric properties (walls density, building area, height) of this type of structure was developed using data from field surveys. This information was complemented with results from experimental tests to compute a large set of capacity curves using a mechanical procedure. These models were tested against a set of ground motion records using the displacement-based earthquake loss assessment (DBELA) procedure, and the structural responses were used to derive fragility functions for four building classes. The resulting fragility curves were convoluted with seismic hazard curves to evaluate the annualized expected loss ratio and annual collapse probability.